PEMBERDAYAAN KADER POSYANDU DALAM UPAYA PENINGKATAN KESEIMBANGAN DINAMIS DENGAN MENGGUNAKAN CORE STABILITY EXERCISE PADA LANSIA - Yoni Rustiana Kusumawati; Budi Utomo; Yuliana Ratmawati (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2023)
Background: Old age is a phase of decreased intellectual and physical abilities, which begins with several changes in life. Elderly is someone who has reached the age of 60 (sixty) years and over Approach Method: Counseling and Empowering Posyandu cadres in an effort to improve dynamic balance by using core stability exercise in the elderly. Place and time: In Guli Village, Nogosari District, Boyolali District, Central Java Province from February to October 2022. Outcome target: Increased understanding and empowerment of posyandu cadres in an effort to improve dynamic balance using core stability exercise in the elderly